Fundamental movement skills and the effects of focus of attention on throwing among autism spectrum disorder children (IR) - Nur Amalina Samsudin (2017)
Although studies have reported on the overall gross motor skills among Autism Spectrum Disorder (ASD) children, limited attempts have been made on examining their throwing skills and the effects of different focus of attention (FoA) instructions on acquiring those skills. This study aimed to compare the Fundamental Movement Skills (FMS) and overhand throw skill between the ASD and Typical Developmental (TD) children. Ten ASD and 10 TD children aged from seven to 10 participated in the study. Test of Gross Motor Development (TGMD-2) was used to measure the FMS of both groups. ANCOVA test with age as covariate showed that the overall gross motor skills score of the ASD children were significantly poorer compared to their TD peers, similarly with the overhand throw subtest data analysis by Independent t-test. Followup study examined the effects of different FoA instructions on performing the throwing skill in a modified-petanque game among the ASD children. They were randomly assigned to two groups, External Focus (EF) and Internal Focus (IF). The EF group were instructed to throw the boules so that it moved in a parabolic trajectory as if they were “creating a rainbow” and land near the target. Meanwhile, the IF group were instructed according to conventional throwing techniques, concentrating on the mechanics of the throwing arm. A factorial two group x two tests mixed between-within ANOVA showed significant interactions with the EF group improved significantly in the post-test compared to the IF counterpart after two weeks of intervention. Simplified yet effective instructions could elicit effective learning among ASD children. Future research could examine the effectiveness of EF instructions on other fundamental skills among special needs children.